OSAMA BIN LADEN: A WAR WAGED WITHIN THE GAPS IN INTERNATIONAL LAW (The Pretoria Student Law Review, 2021)
The recent demise of arch-terrorist Osama bin Laden at the hands of United States (US) Navy Seals has given rise to furious debate as to the legality thereof. The broadest question to ask is whether bin Laden’s killing can be justified in terms of international law. Indeed, it is not even clear which legal paradigm should be utilised to answer this conundrum. In this article it will be shown that the American term, ‘war on terror’, does not fit neatly into the definition of either an international or non-international armed conflict and is therefore not comfortably governed by the rules of either. The concept of selfdefence, desperately needing clarification, will then be proposed as something which operates outside these two paradigms. The aforementioned discussions will lead to an analysis of whether the correct over-arching legal system to apply is international humanitarian law (the law of war) or international human rights law; or whether these two can legitimately operate concurrently. Finally, some brief thoughts will be added regarding the legality of the actual killing of bin Laden.
Keywords: arch-terrorist; Osama bin Laden; United States; legality; international law; ‘war on terror’; international armed conflict; selfdefence; killing of bin Laden; international human rights law